Sampling methods for assessing intra- and inter-genetic diversity in O. glaberrima, O. sativa and O. barthii compared - CGIAR Research Program on Rice (2020)
In 2016, the Rice Biodiversity Center for Africa (RBCA) genotyped 3,255 accessions with 32,000 single nucleotide polymorphisms (SNPs) using DArT-based genotyping by sequencing technology (DArTseq). In 2020, these data were used for comparing different sampling methods for assessing intra- and inter-genetic diversity in O. glaberrima, O. sativa and O. barthii